Coxiella burnetti prosthetic joint infection in an immunocompromised woman: iterative surgeries, prolonged ofloxacin-rifampin treatment and complex reconstruction were needed for the cure - Patrick Miailhes (BMC, 2021)
Abstract Background Q fever is a zoonotic disease caused by the bacterium Coxiella burnetii, a strictly intracellular pathogen that can cause acute and chronic infection. Chronic Q fever can occur in immunocompetent as well as in immuno-compromised hosts, as a persistent localized infection. The main localizations are endocardial, vascular and, less frequently, osteoarticular. The most frequent osteoarticular form is spondyliscitis. Recommended treatment is combined doxycycline and hydroxychloroquine for 18 months, with cotrimoxazole as another option. Coxiella burnetti infection has been implicated in rare cases of prosthetic joint infection (PJI), and the medical and surgical management and outcome in such cases have been little reported. Case presentation We report an unusual case of chronic Q fever involving a hip arthroplasty in an immunocompromised woman treated with tumor necrosis factor (TNF)-α blockers for rheumatoid arthritis. Numerous surgical procedures (explantation, “second look”, femoral resection and revision by megaprosthesis), modification of the immunosuppressant therapy and switch from doxycycline-hydroxychloroquine to prolonged ofloxacin-rifampin combination therapy were needed to achieve reconstruction and treat the PJI, with a follow-up of 7 years. Conclusions Coxiella burnetti PJI is a complex infection that requires dedicated management in an experienced reference center. Combined use of ofloxacin-rifampin can be effective.